Accounting and Tax Treatment of Adjustments for Depreciations or Losses of Value - Nicolaescu, Cristina; Bija, Monica (CECCAR Business Review, 2024)
Throughout their existence, the assets of economic entities may suffer depreciations and in the case of financial assets, value losses may occur. While value losses of financial assets are generally of a temporary nature, for other categories of assets (goods or receivables), depreciations can be either reversible or irreversible. This article focuses on depreciations with a reversible nature, which are accounted for by means of subtractive accounting structures of adjustments for depreciation. The accounting recognition of these structures is crucial in achieving the accounting objective of providing a “true and fair view of the assets and results”, as they correct the historical value of asset elements, the value at which they were recorded upon entry into the entity’s patrimony. The correction involves considering the value of these elements at the reporting moment, usually at the end of the financial year.  As the establishment and increase of adjustment structures, as well as their reduction and cancellation, involve expense and income structures, these operations will have a fiscal impact in certain cases. As a result, the proper sizing and accounting recording of adjustments for depreciation and value loss of asset elements will impact both the reflection of reality in the financial statements and the calculation of income tax payable by economic entities.